Targeting the redistributive payment in selected new European Union member states - Sadłowski, Adrian (Journal of Business Economics and Management, 2022)
The most important element in the recent reform of the Common Agricultural Policy, which is intended to reduce the concentration of aid distributed under the direct support system, is the so-called redistributive payment. The redistributive effects of this instrument depend on its specific form implemented at the national level, the level of funding, and the area structure of holdings in a given country. The objective of this paper is to compare the targeting of the support distributed under the redistributive payment in the three new Member States of the European Union – Bulgaria, Lithuania and Poland. In order to achieve this objective, it was established which area groups of holdings benefit from (and which lose out on) the application of the redistributive payment in each country. In addition, the average amount of support for a holding per hectare of agricultural area, and the percentage change in this support due to the introduction of the redistributive payment, depending on the size of the holding, in individual countries, are shown as a function. The source material was the data made available by the ministries of agriculture of the countries under analysis, relating to 2018.